If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-28=4x-2(-2x-22)
We simplify the equation to the form, which is simple to understand
-28=4x-2(-2x-22)
Reorder the terms in parentheses
-28=4x+(+4x+44)
Remove unnecessary parentheses
-28=+4x+4x+44
We move all terms containing x to the left and all other terms to the right.
-4x-4x=+44+28
We simplify left and right side of the equation.
-8x=+72
We divide both sides of the equation by -8 to get x.
x=-9
| x+2+2x=x | | 8x-20=116-x | | -4 = z-3+ -8 | | 5x-7=3(x+y) | | 6x+8y=140 | | -5c+4(2c+7)=-43 | | 4x^2+16-32=0 | | -(-x+3)= | | [4(x+5)-8]-[3-4(x-2)]= | | 4=-8v+4(v+5) | | -5-3x-7x=-85 | | 6[1-(-3x-9)]=90x+276 | | 45=3(4+y) | | 0.5y+0.9(y+4)=0.3(12) | | 21-7v=6(3-v) | | 7.5n-4(-3-6.4n)=20+37.1 | | 5m-7n+8m-8n= | | 14x+.11y=.124 | | -3(x+2)=-19.5 | | 9-2k=3 | | 7+6x=-1 | | 0=1a-2 | | 3x+4(-5x-5)=-207 | | P=450+.03+3 | | 1y+-6=4 | | 6x+4y=-15 | | 10/1-2/3=x | | 36x^2-12h+1=0 | | 0=9a-2 | | 8(2n+2)=9(9n+5)+3 | | 22x^9-2x^3= | | Y=2(3.14)x |